KARAKTERISASI DAN SKRINING FITOKIMIA AKAR TABAR KEDAYAN (Aristolochiafoveolata Merr.) - Siti Jubidah; Sapri -; Risa Supriningrum (PROSIDING SEMINAR KIMIA, 2013)
East Kalimantan has so much plant diversity of the various ethnic Dayak. One is the Tabar Kedayan plants (Aristolochia foveolata), which empirically efficacious as an antidote (anti-venom). However, its usefulness has not been scientifically confirmed, this is due to the small number of scientific studies on the content of secondary metabolites and bioactive compounds contained in the plant Aristolochia foveolata. Characteristics of simplicianot found in Aristolochia foveolata plant monograph book Materia Medika Indonesia (MMI).This study aimed to investigate the characteristics of botanicals and content ofsecondary metabolites of Aristolochia plants foveolata. This study covers the characteristics of simplicia (byorganoleptic, macroscopic and microscopic) and phytochemical screening (inspection/identification of secondary metabolites) from the plant Aristolochia foveolata. Determination results showed that the samples of plants used are Tabar Kedayan Root(Aristolochia foveolata Merr.). Of the genus Aristolochia and family Aristolochiaceae. Tabar Kedayan root powder contained fragments: fibers, cork fragments, starch items, wooden vessels, parenchyma.Characteristic root extract is obtained Tabar Kedayan; condensed form of oily, brown color, typical aromatic odor, bitter taste, pH 5, specific gravity 1.047 g / ml, 31% shrinkage drying, water-soluble compound 42.5%, compound soluble in ethanol 16.13%, yield 25% extract. Tabar Kedayan root contains compounds alkaloids, flavonoids, saponins, tannins, terpenoids and steroids. TLC method using a spray reagent Dragendorf, showed that positive Tabar Kedayan roots contain the alkaloid compound gives red brick staining with Rf value of 0.96.